Management techniques in Dental Pediatrics: a narrative review of the literature (Research, Society and Development, 2021)
Introduction: this study aims to provide a descriptive explanation of management techniques in pediatric dentistry, which aim to develop a more appropriate behavior in the child while receiving dental treatment. Such conduct is extremely necessary for the professional to be able to carry out the treatment properly and efficiently, without causing harm to the child. Methodology: the descriptors in health science (DeCS / MESH) were used to elaborate the search strategy, which was applied in the PUBMED, SCOPUS and WEB OF SCIENCE databases, being found among all 231 articles. The inclusion criteria for the articles were: addressing in the title the theme of caring for a child in the context of pediatric dentistry and providing a description of some handling techniques with children during the performance of dental procedures used by dentists and assistants. As exclusion criteria, any papers that dealt with purely theoretical aspects, adolescents or that reported sedation techniques were excluded. After removing the duplicates and applying the inclusion and exclusion criteria, 9 articles were allowed. Results and discussions: 8 behavior management techniques were obtained, however, there is a need for technique and theoretical knowledge to choose and use the correct management. Furthermore, to work with children and obtain their cooperation during dental procedures, it is necessary to know and respect each stage of the child's development. Conclusion: the professional must fight the fear of the child by making the office environment something familiar, using the most trained management techniques.